2018
DOI: 10.1002/hep4.1141
|View full text |Cite
|
Sign up to set email alerts
|

Exploring opportunities to prevent cirrhosis admissions in the emergency department: A multicenter multidisciplinary survey

Abstract: Patients with cirrhosis have high admission and readmission rates, and it is estimated that a quarter are potentially preventable. Little data are available regarding nonmedical factors impacting triage decisions in this patient population. This study sought to explore such factors as well as to determine provider perspectives on low‐acuity clinical presentations to the emergency department, including ascites and hepatic encephalopathy. A survey was distributed in four liver transplant centers to both emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…13,14 Similar to previous studies, our present study also demonstrated that the presence of hepatic encephalopathy was the strongest predictor of early readmission to the hospital. 4,6,7,9,11 This consistent observation across studies and across different cohorts is important for several reasons. First, it validates the important predictive ability of hepatic encephalopathy on recurrent hospitalizations.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…13,14 Similar to previous studies, our present study also demonstrated that the presence of hepatic encephalopathy was the strongest predictor of early readmission to the hospital. 4,6,7,9,11 This consistent observation across studies and across different cohorts is important for several reasons. First, it validates the important predictive ability of hepatic encephalopathy on recurrent hospitalizations.…”
Section: Discussionmentioning
confidence: 64%
“…These observations highlight the potential for a systematic targeted quality improvement program to significantly improve hepatic encephalopathy management and overall cirrhosis-related outcomes. 5,11 Another important factor influencing hospital readmission rates among cirrhosis patients involves suboptimal patient awareness and understanding of their disease process. A study by Volk et al 7 reported that 22% of readmissions can be attributed to inadequate patient education about medication dosing (especially in regards to adjusting lactulose) or lack of prompt follow-up labs or clinic visits to adjust diuretics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent interview study of patients with an early readmission for decompensated cirrhosis, the majority stated that they would use a smartphone to manage their condition, particularly if it was able to transmit weight data to their provider [ 13 ]. Retrospective and survey studies suggest that programs with enhanced outpatient care can improve outcomes for patients with ascites [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective and survey studies suggest that programs with enhanced outpatient care can improve outcomes for patients with ascites [14,15].…”
Section: Introductionmentioning
confidence: 99%